2020
DOI: 10.1186/s12989-020-00388-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology changed by 3- and 6-months low-level PM2.5 inhalation exposure in spontaneously hypertensive rats

Abstract: Background Epidemiological evidence has linked fine particulate matter (PM2.5) to neurodegenerative diseases; however, the toxicological evidence remains unclear. The objective of this study was to investigate the effects of PM2.5 on neuropathophysiology in a hypertensive animal model. We examined behavioral alterations (Morris water maze), lipid peroxidation (malondialdehyde (MDA)), tau and autophagy expressions, neuron death, and caspase-3 levels after 3 and 6 months of whole-body exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 75 publications
(95 reference statements)
5
11
0
Order By: Relevance
“…The mean concentration of PM 2.5 was 11.38 μg/m 3 during the entire exposure period in the present study, which was near the WHO guidelines and similar to our previous studies [ 22 , 32 , 33 ]. The composition analysis of our collected PM 2.5 showed that SO 4 2- , NH 4 + , and NO 3 - were the enriched ions, which originate from urban traffic or coal burning [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The mean concentration of PM 2.5 was 11.38 μg/m 3 during the entire exposure period in the present study, which was near the WHO guidelines and similar to our previous studies [ 22 , 32 , 33 ]. The composition analysis of our collected PM 2.5 showed that SO 4 2- , NH 4 + , and NO 3 - were the enriched ions, which originate from urban traffic or coal burning [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…The accumulation of pathological proteins and the related neuronal dysfunction in the olfactory bulb were associated with the occurrence of neuropathology in other brain areas, which may be used an early biomarker for AD and other neurodegenerative diseases [ 57 ]. Our previous studies also showed the elevated p-tau expression in the olfactory bulb of spontaneously hypertensive rats subchronic exposed to low-level PM 2.5 [ 32 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The characteristic uid markers of AD, decreased Aβ42 and increased P-tau protein levels in cerebrospinal uid (CSF), were also reported in urbanites with high exposure to PM 2.5 [11]. Accelerated amyloid plaque deposition and P-tau accumulation have been detected in the brains of animal models after exposure to concentrated air pollutants, especially in the hippocampal area [17,18,19,20,21]. The successive pathways of in ammation, oxidative stress, microglial activation, and even DNA damage are thought to cause this degenerative pathology [17,19,22,23,24].…”
Section: Introductionmentioning
confidence: 98%